Essentialism and the problem of change - Mota Pinto, Silvio (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
This paper discusses the problem of permanence and change. It starts presenting contemporary essentialism as opposed to anti-essentialism and then the notions of existence, identity and change. Finally, it appeals to the nature of predication in order to show that, against the essentialist, the conception of change of his opponent succeeds in solving the problem of the semantic unity of the proposition.
Keywords: essentialism; change; identity; predication; unity of proposition